Relatively normal? Navigating emergent sensitivity in generating and analysing accounts of 'normality'. Issue 5 (3rd September 2021) - Witney, Tom; Keogh, Peter
ABSTRACT: This article describes methodological and ethical issues associated with examining discourses of 'normality' in the context of the normalisation of HIV and relationships. It considers how sensitivity was anticipated, encountered and managed in the recruitment of participants and during research interviews, discussing the implications of these in this project. It reflects on the tensions present when generating data on topics externally deemed to be 'sensitive' but considered 'normal' by participants. In doing so, it has wider relevance for research on experiences that were once prohibited but are now considered normative in some settings, such as gay marriage. However, highlighting the importance of 'the normal' in notions of stigma, it concludes that potentially any research project that examines or questions 'normality' may give rise to sensitivity, emphasising the importance of reflexivity in assessing and managing sensitivity throughout the research process.